Revisión bibliográfica de la aplicación de la metodología DEA en Colombia por actividad económica (2017)
This article presents the results of a bibliographic review of the national intellectual production associated to the application of the Data Envelopment Analysis (DEA) methodology in Colombia and the International Standard Industrial Classification (ISIC) adapted for the country. From this review, the characteristics of the objects of study of the investigations are established and it is shown how the methodology is used. In conclusion, it is necessary that, although the management of DEA has been increased, it is still incipient and, therefore, there are several research opportunities that include different types of Decision Making Units (DMU).